Advances in ecological research - Begon, Michael; Fitter, Alastair; Ford, E. D. (Edward David); Macfadyen, A. (Amyan) (Advances in ecological research ;, 1989)
Volume 19 in this prestigious series is the second under the new editorial team and benefits once again from their own special interests. The scope of this volume is wide, spanning aspects of plant/insect interactions and arthropod population dynamics to palaeobotany, the evolution of photosynthesis, and marine community ecology. Of particular topical interest is an article on the impact of rising levels of atmospheric carbon dioxide on tree physiology.